Feasibility of avian antibodies as prophylaxis against enterotoxigenic escherichia coli colonization - Brumfield, Kyle; Seo, Hyesuk; Idegwu, Nnebuefe; Artman, Chad; Gonyar, Laura; Nataro, James; Zhang, Weiping; Sack, David; Geyer, James; Goepp, Julius (Frontiers in Immunology, 2022)
Abstract Background: This research aims to evaluate the feasibility of using avian immunoglobulins (IgY) raised against adhesion factors of enterotoxigenic Escherichia coli (ETEC) as prophylaxis of diarrheal illness caused by these pathogens. ETEC requires adhesion to human intestinal epithelial cells as a primary step in establishing enteric infection. Therefore, inhibition of adhesion may prevent such infections and reduce clinical burdens of diarrheal illness. Methods: IgY samples were prepared from eggs of hens immunized with an adhesin-tip multiepitope fusion antigen (MEFA), developed against nine adhesin tip epitopes derived from clinically relevant ETEC strains. The resulting IgY was evaluated for its ability to inhibit adhesion of ETEC to cell-surface targets. Potential impacts of anti-MEFA IgY on growth of both pathogenic and commensal E. coli isolates were also evaluated. Results: Enzyme linked immunosorbent assay (ELISA) titers were achieved for IgY targeting each of the nine individual epitopes included in the adhesin-tip MEFA. Furthermore, anti-MEFA titers exceeding 1:219 were sustained for at least 23 weeks. All ETEC strains used in design of the adhesin-tip MEFA, and five of five clinical ETEC strains were significantly (P < 0.05) inhibited from adhesion to mammalian cells in culture. Conclusions: These findings demonstrate that IgY targeting ETEC adhesin-tip MEFA have the potential to disrupt in vitro adherence of ETEC. A formulation containing adhesin-tip MEFA IgY can be considered a potential candidate for in vivo evaluation as prophylaxis of diarrheal diseases. Animal studies of this formulation are planned.